Lessons from the Asian Crisis: A Central Banker's Perspective - Laurence H. Meyer (Levy Economics Institute of Bard College, 1999)
This paper presents a central banker's perspective on the Asian crisis. Central banks have two core missions: the pursuit of monetary policy to achieve broad macroeconomic objectives and the maintenance of financial stability, including the management of financial crises. The management of financial crises is closely connected to the regulation and supervision of the banking system, so it, as well as broader issues related to systemic risk in the financial sector, is included as part of the central banker's perspective. Central banks also often have or share with finance ministries control over exchange rate policy, including the choice of an exchange rate regime and the management of that regime. Therefore, the roles of exchange rate policy, macroeconomic policy, and bank supervision and regulation in the crises are examined and some lessons in each case are suggested. The author's interpretation of the sources of and appropriate policy responses to the crises among the Asian emerging economies draws heavily upon the work of Hyman P. Minsky.
Keywords: 330